Bifunctional silica nanoparticles for the exploration of Pseudomonas aeruginosa biofilm - Mauline, L.; Gressier, M.; Hammer, P. [UNESP]; Ribeiro, S. J. L. [UNESP]; Caiut, J. M. A.; Menu, M. -J.; Roques, C.; IEEE (Ieee, 2016)
Luminescent silica nanoparticles (LSNPs) are frequently employed for biotechnology applications mainly because of easy functionalization, photo-stability and biocompatibility. Bifunctional silica nanoparticles (BSNPs) are described here as new efficient tools for the understanding of a complex biological system such as biofilms. Photoluminescence is brought by the incorporation of a silylated ruthenium(II) complex, surface properties of the silica particles are designed by reaction with. BSNPs are fully characterized and Zeta potential and contact angle measurements exhibit various surface properties according to the functional groups. Confocal Laser Scanning Microscopy measurements show that the spatial distribution of these nanoparticles inside PAO1 biofilm depends more on their hydrophilic/hydrophobic characteristics than on their size.